'Selling' national security: Saab, YouTube, and the militarized neutrality of Swedish citizen identity. Issue 3 (3rd July 2019) - Jackson, Susan T.
ABSTRACT: Producers of large conventional weapons systems are significant actors in politics and their presence in everyday life is a potential site of militarization, yet they remain remarkably understudied in International Relations (IR) research. Though the public cannot purchase their products, 88 of the top 100 arms producers use official corporate YouTube channels to reach the public. Their YouTube videos are political artefacts that these companies use to 'sell' national security as military security, framing the military as a 'good, natural, and necessary' part of society. Examining these videos reveals how this messaging can be conceptualized as a type of militarization because of the relation 'good, natural, and necessary' has to national security constructions. I use an intersectional lens and a multi-modal audio-visual approach to understand how images, sounds, and texts work together to tell a version of Sweden's national security story as constructed in Saab's official corporate YouTube videos. These videos illuminate a view that Sweden does (and should ) have militarized national security that seems counter to images of a peacekeeping nation. This national security is centred on a citizen identity that consists of masculinized, heteronormative, and nationally hierarchical constructions of militarized national security.